Level of knowledge about information searching in health professional - Ana María Molina Gómez; María Elinor Dulzaides Iglesias; Oristela Mora Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: the accelerated growing of the importance and the amount of the information do not allow accumulating and storing all the information needed. It demands the development of abilities to take them back, understand them, and place them in the adequate format in the case of those needed for its organization or for the individual. Objective: to measure the level of knowledge about information searching in health professionals. Methods: a descriptive, transversal study carried out in the library of the medicine school in Cienfuegos city from March to May 2007. It included 100 users selected at simple random. Characterization of the sample, perception of the users about the knowledge on the steps to make to perform a search, main medical web sites and how to search for the information in INFOMED, sites and data bases in which they carry out the search, knowledge of elements, sites and tools for searching were the variables analyzed. The data were obtained from a survey and processed on Microsoft Excel system. Results: only 48 % of the users master the steps to carry out a search, 46 % stated to know the main medical web sites and, 61 % of them declared to know how to make a search in INFOMED which was the most visited web site. 58 % of the users do not have the abilities for an effective information search. Conclusions: our professionals have a low level of knowledge about information searching and medical web sites.